Enhanced performance of hybrid piezo/triboelectric using BaTiO3/polymer composite film modified with rGO - Panpho, Phakakorn; Phetphong, Pornphiphat; Charoonsuk, Thitirat; Vittayakorn, Narathip; Sriwong, Chaval; Sumang, Rattiphon (My University, 2024)
Hybrid piezo/triboelectric technology is an emerging energy source that can continuously power small electronic devices by harvesting ambient mechanical energy and converting it into electricity. In this work, a high-performance hybrid piezo/triboelectric device was presented. The composite film was synthesized that co-doped BaTiO3 powders (BT) and reduced graphene oxide (rGO) embedded within a host material made of polydimethylsiloxane (PDMS). The hybrid device is made by mixing BT powders into the PDMS to form a series of composite films, ranging from 10% to 45% by wt.%. Additionally, 1–5 wt.% of rGO was loaded into fabricates 40BT/PDMS. The results show that the addition of rGO can improve the uniform dispersion of BT powder in the PDMS matrix. The 4 wt.% of rGO for 40BT/PDMS exhibited the optimal energy harvesting performance among all compositions, achieving notable output voltage and current. This work demonstrates a facile, low-cost approach for obtaining high-performance hybrid piezo/triboelectric by utilizing a composite film BaTiO3 and polymer (PDMS) modified with rGO.
Keywords: BaTiO3; hybrid piezo/triboelectric; PDMS polymer; rGO; structure and morphology